The metaphysics of 18th century natural religion - Curtin, Thomas John (Trinity College (Dublin, Ireland). Philosophy Department, 2011)
The main focus of this dissertation concerns the influence that Malebranche's conception of causation, which understands causal power in terms of absolute necessity, had upon the writings of George Berkeley and David Hume, and the specific manner in which each philosopher responds to that conception within the context of natural religion. I argue for two main claims. First, that Berkeley rejects Malebranche's conception of a true cause and defines causal power in terms of volition in order to shelter his natural religion from the threat he foresaw in the modeling of causation upon absolute necessity.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin.